2015
DOI: 10.2519/jospt.2015.5583
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict Which Patients With Patellofemoral Pain Are More Likely to Benefit From Exercise Therapy? A Secondary Exploratory Analysis of a Randomized Controlled Trial

Abstract: Two factors, sex and duration of complaints, may have a predictive value for response to exercise therapy at 3-month follow-up. Due to the exploratory design of the study, future research should confirm this tendency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Six different specific treatments were investigated; foot orthoses,30 32 33 45–47 lumbopelvic manipulation,34 48 patellar taping,31 femoral nerve mobilisation,49 leg press exercise and stretching28 and exercise therapy (consisting of static and dynamic exercises for the quadriceps muscles, flexibility and balance exercises)50 (table 2). Twenty-two patient characteristics were reported to be associated with a successful outcome after a specific treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six different specific treatments were investigated; foot orthoses,30 32 33 45–47 lumbopelvic manipulation,34 48 patellar taping,31 femoral nerve mobilisation,49 leg press exercise and stretching28 and exercise therapy (consisting of static and dynamic exercises for the quadriceps muscles, flexibility and balance exercises)50 (table 2). Twenty-two patient characteristics were reported to be associated with a successful outcome after a specific treatment.…”
Section: Resultsmentioning
confidence: 99%
“…One study compared exercise therapy with usual care and found no significant predictors of a successful outcome to exercise therapy 50. One study evaluated a leg press training and lower limb muscle stretching exercise programme 28.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment outcomes may be different on the basis of some characteristics (ie, effect modification). Lankhorst et al 53 suggested that sex and symptom duration may be effect modifiers in the relationship between exercise and function at 3 months, but no significant association was found. As there is no good evidence for any potential effect modifier, we did not include potential effect modifiers when planning the synthesis.…”
Section: Strengths and Weaknesses Of This Studymentioning
confidence: 99%
“…Several recent studies have established which patients are most likely to experience favourable outcomes with different conservative treatment approaches36,37,38 ) . A longer duration of symptoms (>4 months) will most likely result in a poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Other prognostic factors include older age, greater usual pain severity and lower baseline AKPS score38 ) . One study37 ) found that females respond better than males to exercise therapy. Kinematic differences may exist between genders.…”
Section: Discussionmentioning
confidence: 99%